Business Takeover or New Venture? (Why) Do Women Prefer New Ventures? - Kay, Rosemarie; Schlömer-Laufen, Nadine (Senate Hall, 2016)
This paper analyzes the role of (nascent) entrepreneurs' sex in choosing the mode of business entry. Using a unique data set and estimating logit regressions we show that nas-cent entrepreneurs' sex indeed affects their intended and actually chosen mode of entry. Compared to men, women are less likely to (intend to) take over a business than to start one from scratch because of gender differences in nascent entrepreneurs' resources (specific qualifications, time resources, and the capability of opportunity recognition) and other factors which affect the mode of entry. Though women are an underutilized potential as family business successors, tapping this potential requires fundamental societal changes, e.g. in regard to the gender-related division of labor and vocational choice. Keywords: mode of business entry, gender, resources, business creation process
Keywords: mode of business entry|gender|resources|business creation process